Problems with Periodic Table Theory-Praxis in Chemistry Topics Teaching - Mhlongo, Thabo; Sedumedi, Thomas Dipogiso (Indonesian Journal of Science and Mathematics Education, 2023)
The two main chemical concepts that are the subject of this investigation are chemical bonds and related reactions. This research examines how the periodic table concept can help teachers improve science teaching. To help students understand the contents of the periodic table and the helpful information its settings provide students. This study looks at how teachers use the periodic table in class. The study focused on schools as a single case and adopted a qualitative methodological approach. Two physics teachers participated. It was found that according to teachers, the periodic table may impact how they use or ignore its use when teaching students about its content or as a framework for understanding material and chemical reactions. Therefore, the concept of the periodic table can help teachers improve the quality of teaching. There needs to be more in-depth research on the apparent relationship between teacher knowledge representation in chemistry and teachers' approaches to teaching using the periodic table.